German Bowel Cancer Center: An Attempt to Improve Treatment Quality. (3rd May 2015) - Jannasch, Olof; Udelnow, Andrej; Wolff, Stefanie; Lippert, Hans; Mroczkowski, Pawel
Abstract : Background . Colorectal cancer remains the second most common cause of death from malignancies, but treatment results show high diversity. Certified bowel cancer centres (BCC) are the basis of a German project for improvement of treatment. The aim of this study was to analyze if certification would enhance short-term outcome in rectal cancer surgery. Material and Methods . This quality assurance study included 8197 patients with rectal cancer treated between 1 January 2008 and 31 December 2010. We compared cohorts treated in certified and noncertified hospitals regarding preoperative variables and perioperative outcomes. Outcomes were verified by matched-pair analysis. Results . Patients of noncertified hospitals had higher ASA-scores, higher prevalence of risk factors, more distant metastases, lower tumour localization, lower frequency of pelvic MRI, and higher frequencies of missing values and undetermined TNM classifications (significant differences only). Outcome analysis revealed more general complications in certified hospitals (20.3% versus 17.4%, p = 0.03 ). Both cohorts did not differ significantly in percentage of R0-resections, intraoperative complications, anastomotic leakage, in-hospital death, and abdominal wall dehiscence. Conclusions . The concept of BCC is a step towards improving the structural and procedural quality. This is a good basis for improving outcome quality but cannot replace it. For a primary surgical disease like rectal cancer a specific, surgery-targeted program is still needed.